Analisis Biaya Produksi Berbasis Pendekatan Variable Costing pada UMKM Catering Dapur Mutiara - Zulfatillah, Auliya; Basyari, Alif Sulthon; Cahyadi, Nur (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2024)
The purpose of this research is to analyze how to estimate production costs at the Dapur Mutiara Catering business in October 2023 using a variable costing approach. Cost analysis with the variable costing method is a calculation of production costs that only includes variable cost elements. The method used in the research is a qualitative method with a case study approach. Through cost analysis and preparation of income statements, the study concludes that the sales value of Dapur Mutiara in October 2023 was Rp 20,332,000 with total variable costs to produce the products is Rp 15,113,000, thus in that period the contribution margin value was Rp 5,219,000 with a contribution profit ratio on sales reaching 25.67%. Meanwhile, the total fixed costs reached Rp 500,000, resulting in a net profit value of Rp 4,719,000. Thus, the profit target of 35% targeted by the business owner has not been achieved because the percentage value of net profit on sales is only 23.21%, this happens because the production costs are too high and the selling price is set too low.